BUSINESS TO BUSINESS MARKET RESEARCH - Ruth Mcnail (Kogan Page Limited, 2005)
This book, Business to Business Market Research is written as a standalone reference document and as part of the new series of books designed for market researchers, market research students and nonprofessional researchers who may have an interest in research, or more particularly, business to business research. The series – under the aegis of The Market Research Society and Kogan Page, the publisher – is intended to help readers learn from others’ experience, develop core skills, apply market research effectively and provide the latest information on research techniques, use of market research and global activity.